Study of evolution for 3D structured surface with nano-balls and walls-like features with thickness variation for WO3 thin films made by spray deposition - Mirela Petruta Suchea; Ioan Valentin Tudose; Cosmin Romanitan; Cristina Pachiu; Marian Popescu; Kyriakos Mouratis; Marina Manica; Stefan Antohe; Stelios Couris; Dragos Gabriel Zisopol; Octavian Narcis Ionescu; Emmanuel Koudoumas (Scientific Reports)
Abstract The present work regards a unique yet study of 3D structured surface evolution of nano-balls and walls-like features with thickness variation, for tungsten oxide (WO3) thin films made by spray deposition. Since in most optoelectronic applications the surface morphology and structure play a crucial role and WO3 is one of the most studied and used metal oxide semiconductors in a significant variety of optoelectronic applications, a detailed study of recently observed and reported unique 3D complex architecture of WO3 coatings fabricated by spray pyrolysis (starting from different precursors) is of great importance for further development of thin film coatings and devices. In this scope, two different series of WO3 of 11 samples with different thicknesses each, starting from two tungsten peroxide precursor concentrations (0.05 M and 0.1 M) were fabricated by spray pyrolysis and thoroughly characterized by field emission scanning electron microscopy (FE-SEM), X-ray diffraction and Raman spectroscopy. Results suggest that, for the mentioned concentrations, the main structural differences affect mostly the surface morphology and slightly the surface texturing. These observations prove the reliability of fabrication of coatings with such surface morphology by spray pyrolysis method and open new perspectives for better sensors, electrochromic or photochromic devices, and more.